The Effect of Social Influence, Perceived Usefulness, and Financial Risk on Intention in Using OVO - Marcelina Audrina Tiffany; Nuryasman M. N. (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to examine the effect of social influence, perceived usefulness and financial risk, as well as age-moderated social influence on the behavioural intention in using OVO from Universitas Tarumanagara students. This study uses data collected from 68 respondents. The method used in this study is cross-sectional with a sample selection technique using purposive sampling. The data in this study were obtained by distributing online questionnaires which were then processed using SmartPLS software version 3.3.3. The results of this study are that social influence and perceived usefulness have a positive influence on behavioural intention in using OVO, and age successfully moderates social influence on behavioural intention in using OVO. Meanwhile, financial risk has no effect on behavioural intention in using OVO.